Answer:
A. $12,000
B. $147,000
Step-by-step explanation:
Answer:
B) x = e^x
Step-by-step explanation:
The graphs of y = e^x and y = x never intersect, so the solution set will be the empty (null) set for ...
x = e^x
_____
There is one intersection of y=x with cos(x) and with sin(x). There are an infinite number of solutions for x = tan(x).
A triangle is a three-edged polygon with three vertices. It is a fundamental form in geometry. The correct option is A.
<h3>What is a triangle?</h3>
A triangle is a three-edged polygon with three vertices. It is a fundamental form in geometry. The sum of all the angles of a triangle is always equal to 180°.
The length of different sides are:
![AB = \sqrt{(5-1)^2+(-4-2)^2} = \sqrt{16+36} = \sqrt{52}\rm\ units](https://tex.z-dn.net/?f=AB%20%3D%20%5Csqrt%7B%285-1%29%5E2%2B%28-4-2%29%5E2%7D%20%3D%20%5Csqrt%7B16%2B36%7D%20%3D%20%5Csqrt%7B52%7D%5Crm%5C%20units)
![BC = \sqrt{(-3-5)^2+(2+4)^2} = \sqrt{64+36} = 10\rm\ units](https://tex.z-dn.net/?f=BC%20%3D%20%5Csqrt%7B%28-3-5%29%5E2%2B%282%2B4%29%5E2%7D%20%3D%20%5Csqrt%7B64%2B36%7D%20%3D%2010%5Crm%5C%20units)
![AC = \sqrt{(2-2)^2+(-3-1)^2} = \sqrt{16} = 4\rm\ units](https://tex.z-dn.net/?f=AC%20%3D%20%5Csqrt%7B%282-2%29%5E2%2B%28-3-1%29%5E2%7D%20%3D%20%5Csqrt%7B16%7D%20%3D%204%5Crm%5C%20units)
Since the length of all the sides of the triangle is not equal it is a scalene triangle.
Hence, the correct option is A.
Learn more about Triangle:
brainly.com/question/2773823
#SPJ1
Answer:Robert's minimum age is 11 years.
Step-by-step explanation:
Let x represent George's age.
Let y represent Edward's age.
Let z represent Robert's age.
George is twice as old as Edward. It means that
x = 2y
Edward's age exceeds Robert's age by 4 years. It means that
z = y - 4
If the sum of the three ages is at least 56 years, it means that
x + y + z ≥ 56 - - - - - - - - - - 1
Substituting x = 2y and z = y - 4 into equation 1, it becomes
2y + y + y - 4 ≥ 56
4y - 4 ≥ 56
4y ≥ 56 + 4
y ≥ 60/4
y ≥ 15
z = y - 4 = 15 - 4
z ≥ 11
Answer:
28y^3 -35y^5
Step-by-step explanation:
= 7y^3(4) -7y^3(5y^2)
= 28y^3 -35y^5
_____
The applicable rule of exponents is ...
(y^a)(y^b) = y^(a+b)